PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK STORYTELLING DALAM MENUMBUHKAN KEBERMAKNAAN HIDUP PADA ANAK PENDERITA KANKER DI RUMAH SEHAT CERIA YKASS - Dwi Indah Salsabilah; Zhila Jannati; Bela Janare Putra (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
Children with cancer face various physical, psychological, and social challenges that may affect their ability to find meaning in life. These challenges are often reflected in decreased motivation, feelings of hopelessness, and difficulties in accepting their condition. This study aimed to describe the level of meaningfulness of life among children with cancer before receiving group guidance services using the storytelling technique, explain the implementation process of the intervention, and identify changes in their sense of life meaning after the intervention. The study employed a qualitative approach with a case study method conducted at Rumah Sehat Ceria YKASS. The participants consisted of five children diagnosed with cancer and other chronic illnesses. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using descriptive qualitative techniques. The findings revealed that prior to the intervention, most participants demonstrated a low sense of life meaning, characterized by limited motivation, poor self-acceptance, and difficulties in interpreting their illness experiences positively. The group guidance service using the storytelling technique was implemented through six sessions involving inspirational storytelling, experience sharing, group discussions, and self-reflection activities. Through these activities, participants were provided with opportunities to express their feelings, build hope, and develop a more positive understanding of their lives. Following the intervention, participants showed positive changes, including increased motivation, greater optimism about the future, improved self-acceptance, enhanced emotional expression, and a more constructive outlook toward life despite their illness. These findings indicate that group guidance services using the storytelling technique can serve as an effective psychosocial intervention to foster a sense of meaning in life among children with cancer and other chronic illnesses, thereby supporting their psychological well-being.